Enhancement of 3-hydroxypropionic acid production from glycerol by using a metabolic toggle switch. Issue 1 (December 2015) - Tsuruno, Keigo; Honjo, Hiroshi; Hanai, Taizo
Abstract Background 3-hydroxypropionic acid (3-HP) is an important platform for the production of C3 chemicals, including acrylic acid, methyl acrylate, and acrylamide. Microbial production of 3-HP is mainly due to glycerol metabolism. In this study, in order to improve microbial 3-HP production, we applied a metabolic toggle switch for controlling the glycerol metabolism to redirect the excess metabolic flux of central metabolic pathway toward an exogenous 3-HP producing pathway inEscherichia coli . Results The metabolic toggle switch enables conditional repression of the expression of a target gene during the fermentation. We individually performed conditional repression ofglpK, tpiA, andgapA, which are involved in glycerol metabolism. The conditional repression ofglpK andtpiA was not effective for 3-HP production under our experimental conditions. However, gapA conditional repression contributed to improve 3-HP production (titer, 54.2 ± 1.5 mM; yield, 32.1 ± 1.3 %) compared with that for the wild type strain. Additional deletion of endogenousyqhD, which is responsible for the production of a major byproduct, 1, 3-propandiol, further increased 3-HP production (titer, 67.3 ± 2.1 mM; yield, 51.5 ± 3.2 %). The titer and yield were 80 and 94 % higher than those of the wild type strain, respectively. The obtained 3-HP yield from glycerol is comparable with the highest yield ever reported for microbial 3-HP production using glycerol as a sole carbon source. The measurement of intracellular metabolites showed the metabolic toggle switch successfully controlled the metabolic flux. Conclusion The conditional repression ofgapA by using the metabolic toggle switch combined with deletion of endogeneousyqhD increased 3-HP production approximately twofold from glycerol. This result indicates the metabolic toggle switch can be applied in various bio-production using diverse substrates.